TANGGUNG JAWAB HUKUM ANAK DI BAWAH UMUR DALAM HAL TERJADINYA KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN KORBAN JIWA - Feni Christin (Fakultas Hukum Universitas Tarumanagara, 2021)
Children are a mandate and gift from God Almighty, who has the dignity and worth as a whole human being. The Involvement of a child in legal matters can make society insensitive to justice and underestimate the role of children as the nation's next generation. This condition should be a deep concern for parents in accompanying and supervising the behavior of children. A child is someone who is immature both mentally and physically, who still needs to be guided and supervised in his association. This ignorance of children often makes children do deviant behaviors and tend to do evil. Behavior that deviates from the norm will usually create a new problem in the legal field and harm society. Traffic accidents are one of the deviant behaviors of children. As a result of his actions he must be responsible for himself. Regarding traffic accidents, in Indonesia in 2021 there will be approximately 1,291 cases or this figure is up 100 percent from 2020eb, and most of these accidents are caused by minors.